Creative Network Communities in the Translocal Space of Digital Networks - Smite, Rasa (Human Technology, 2013)
What should sociological research be in the age of Web 2.0? Considering that the task of "network sociology" is not only empirical research but also the interpretation of tendencies of the network culture, this research explores the rise of network communities within Eastern and Western Europe in the early Internet era. I coined the term creative networks to distinguish these early creative and social activities from today's popular social networking. Thus I aimed to interpret the meaning of social action; the motivation of creative community actors, their main fields of activities and social organization forms; and the potential that these early developments contain for the future sustainability of networks. Data comprise interviews with networking experts and founders and members of various networks. Investigating respondents' motivations for creating online networks and communities, and interpreting those terms, allows for comparing the creative networks of the 1990s with today's social networks and for drawing conclusions.